Apical Extrusion of Irrigants in Immature Permanent Teeth by Using EndoVac and Needle Irrigation: An In Vitro Study. - N Velmurugan; C Sooriaprakas; Preetham Jain (Tehran University of Medical Sciences, 2014)
Immature teeth have a large apical opening and thin divergent or parallel dentinal walls; hence, with conventional needle irrigation there is a very high possibility of extrusion. This study was done to compare the apical extrusion of NaOCl in an immature root delivered using EndoVac and needle irrigation.Eighty freshly extracted maxillary central incisors were decoronated followed by access cavity preparation. Modified organotypic protocol was performed to create an open apex; then, the samples were divided into four groups (n=20): EndoVac Microcannula (group I), EndoVac Macrocannula (group II), NaviTip irrigation needle (group III) and Max-i-Probe Irrigating needle (group IV); 9.0 ml of 3% sodium hypochlorite was delivered slowly over a period of 60 seconds. Extruded irrigants were collected in a vial and analysed statistically.Group I, group III and group IV showed 100% extrusion (20/20) but group II showed only 40% extrusion (8/20). The difference in this respect between group II and other groups was statistically significant (P